2020
DOI: 10.31219/osf.io/9zf7y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reporting of Drug Trial Funding Sources and Author Financial Conflicts of Interest in Cochrane and non-Cochrane Meta-analyses: A Cross-sectional Study

Abstract: Background: A previous study found that 2 of 29 (6.9%) meta-analyses published in high-impact journals in 2009 reported included drug trials’ funding sources, and none reported trial authors’ financial conflicts of interest (FCOIs) or industry employment. It is not known if reporting has improved since 2009. Our objectives were to (1) investigate the extent to which pharmaceutical industry funding and author-industry FCOIs and employment from included drug trials are reported in meta-analyses published in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…We evaluated 3 Cochrane reviews, and all 3 reported trial funding sources, but only 1 of 3 provided information on author-industry financial ties from included trials. A recent study [52] that investigated the extent to which recently published meta-analyses reported trial funding, authorindustry financial ties, and author-industry employment from included RCTs found that reporting of trial funding in Cochrane meta-analyses increased from 30% (46 of 151 reviews) in 2010 to 84% (90 of 107) in 2016-2018. Reporting of trial author-industry financial ties increased from 7% (11 of 151) in 2010 to 44% (47 of 107) in 2016-2018, which suggests that this could still improve.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated 3 Cochrane reviews, and all 3 reported trial funding sources, but only 1 of 3 provided information on author-industry financial ties from included trials. A recent study [52] that investigated the extent to which recently published meta-analyses reported trial funding, authorindustry financial ties, and author-industry employment from included RCTs found that reporting of trial funding in Cochrane meta-analyses increased from 30% (46 of 151 reviews) in 2010 to 84% (90 of 107) in 2016-2018. Reporting of trial author-industry financial ties increased from 7% (11 of 151) in 2010 to 44% (47 of 107) in 2016-2018, which suggests that this could still improve.…”
Section: Discussionmentioning
confidence: 99%